A National Profile of Tourette Syndrome, 2011–2012 - Bitsko, Rebecca H. (J Dev Behav Pediatr, 2014)
OBJECTIVE: To provide recent estimates of the prevalence of Tourette Syndrome among a nationally representative sample of US children, and to describe the association of Tourette Syndrome with indicators of health and functioning. METHOD: Data on 65,540 US children aged 6–17 years from the 2011–2012 National Survey of Children s Health were analyzed. Parents reported whether a health care provider had ever told them their child had Tourette Syndrome or other neurobehavioral or chronic health conditions, and whether their child had current Tourette Syndrome. RESULTS: Based on parent report, 0.19% of US children had Tourette Syndrome; the average age of diagnosis was 8.1 years. Children with Tourette Syndrome, compared to those without, were more likely to have co-occurring neurobehavioral and other health conditions, meet criteria for designation as having a special health care need, receive mental health treatment, have unmet mental health care needs and have parents with high parenting aggravation and parents who were contacted about school problems; they were less likely to receive effective care coordination or have a medical home. After controlling for co-occurring neurobehavioral conditions, the findings on parents being contacted about school problems and children having unmet mental health care needs were no longer significant. CONCLUSION: TS is characterized by co-occurring neurobehavioral and other health conditions, and poorer health, education and family relationships. The findings support previous recommendations to consider co-occurring conditions in the diagnosis and treatment of Tourette Syndrome. Future research may explore whether having a medical home improves outcomes among children with Tourette Syndrome.